Subcutaneous Emphysema in a Healthy Child: An Unusual Clue for the Diagnosis of Foreign Body Aspiration - Seied Mohsen Emami; Mohammad Shurideh Yazdi; Reza Jafarzadeh Esfehani (Mashhad University of Medical Sciences, 2017)
Background: Spontaneous pneumomediastinum (SPM) and subcutaneous emphysema are rare findings in children. Various etiologies have been reported for SPM, such as foreign body aspiration in infants, especially in those aged less than three years. In addition to the complications associated with foreign body aspiration, SPM may also become a life-threatening condition if left untreated. In the present report, we discussed a case of subcutaneous emphysema, pneumothorax, and pneumomediastinum in a 13-month-old infant previously treated for pneumonia.Case report: The infant was initially presented with subcutaneous emphysema of the neck, without respiratory distress following pneumonia. In the chest radiography, mediastinal shift and possible pneumothorax were reported, and a chest tube was inserted as the respiratory condition deteriorated. Emergency bronchoscopy showed a foreign body logged in the left respiratory tract, which was removed. Three days later, the chest tube was detached, and the patient was discharged in healthy conditions within the next two days.Conclusion: Pediatricians constantly need to consider the risk of foreign body aspiration, particularly in the presence of respiratory complications, such as SPM, even in the infants with an unreliable history of foreign body aspiration